For environmental monitors, relationships matter in multiple ways: insights from a research collaboration in South Africa - Rosenberg, Eureta; Mtati, Nosiseko; Cockburn, Jessica (Frontiers in Environmental Science, 2024)
The literature identifies several challenges facing natural resource management collaboration, from structural conditions like corruption to divergent interests, skewed decision-making powers and logistical, communications and information failures. The case study on which we base this paper examines a successful collaboration between university-based scientists and citizen environmental monitors in a rural region of South Africa. The Tsitsa project aimed to create benefits for people and environment, through collaborative research towards sustainable natural resource management. However, collaboration was not a given, and the lessons learnt in this regard form the gist of the paper. Using a relational realist lens, we conduct a secondary analysis of a case study undertaken in 2020-2021, into what the Tsitsa citizen monitors valued. It proved vital that researchers approached monitors in ways that communicated care, respect and trust, such as addressing them in their own language, being available for follow-ups, and paying for their work. When relational aspects were taken care of, collaboration flowed, and it was evident that citizen monitors share with scientists core human values: family, social standing through contribution, friendships and stimulating work, an interest in the environment and pride in a job well done. Our practice-based insights into the causal powers of relationships and the value of careful relationship-building for more sustainable and just natural resource management relationships adds to the emerging body of work on relationality in the sustainability sciences.